Physico-Chemical Characterisation Of Mangrove Tannins As Corrosion Inhibitors [QD327. A257 2005 f rb]. - Rahim, Afidah Abdul (2005)

(untitled)
Tannins from mangrove barks have been successfully extracted using 70 % aqueous acetone and purification by LH-20 column chromatography afforded condensed tannins of high purity.